Atlas of soft tissue tumor pathology - Fisher, Cyril (Atlas of Anatomic Pathology, 2013)
Soft tissue tumors are a large and heterogeneous group of tumors and pseudotumors with a spectrum of behavior from benign to frankly malignant.  This Atlas of Soft Tissue Tumor Pathology provides an overview of reactive, pseudoneoplastic, benign and intermediate neoplasms, sarcomas and related conditions arising in subcutaneous and deep soft tissues. Emphasis is placed on microscopic appearances with correlation with gross diagnostic findings where relevant. In addition, the immunohistochemical and molecular genetic features of the major soft tissue tumor subtypes are presented. This compendium of soft tissue tumors illustrates the vast majority of diseases you are likely to encounter in surgical pathology.